2012
DOI: 10.1002/jrs.4200
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformations in CaCO3/iron oxide composite induced by thermal treatment and laser irradiation

Abstract: Calcium carbonate (CaCO3)/iron oxide composites were synthesized through a simple one‐step impregnation procedure by mixing iron oxide nanoparticles (γ‐Fe2O3 and Fe3O4) of about 6 nm in size and CaCO3 microparticles (Φ = 2 µm–8 µm, vaterite phase). The morphology and structural properties of CaCO3, iron oxide nanoparticles and CaCO3/iron oxide composites were characterized as a function of low iron content (0 %w to 3.2 %w) by scanning electron microscopy and transmission electron microscopy, X‐ray diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Indeed, it is noted that Ca 2 Fe 2 O 5 brownmillerite-type phase (srebrodolskite) formation can occur as a consequence of Fe 2 O 3 and CaO reaction (eqn (3)), whilst the formation of mineral srebrodolskite is in agreement with previous work on CaO:Fe 2 O 3 thermal processing. 22,24 In particular, Boyanov, 24 reporting on the formation of calcium ferrites (Ca 2 Fe 2 O 5 and CaFe 2 O 4 ) in the range of 900-1200 1C, investigated by HT-XRD, noted complete consumption of CaO:Fe 2 O 3 by 1200 1C. This balance helps to explain the presence of residual Fe 2 O 3 peaks at 1050 1C in Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, it is noted that Ca 2 Fe 2 O 5 brownmillerite-type phase (srebrodolskite) formation can occur as a consequence of Fe 2 O 3 and CaO reaction (eqn (3)), whilst the formation of mineral srebrodolskite is in agreement with previous work on CaO:Fe 2 O 3 thermal processing. 22,24 In particular, Boyanov, 24 reporting on the formation of calcium ferrites (Ca 2 Fe 2 O 5 and CaFe 2 O 4 ) in the range of 900-1200 1C, investigated by HT-XRD, noted complete consumption of CaO:Fe 2 O 3 by 1200 1C. This balance helps to explain the presence of residual Fe 2 O 3 peaks at 1050 1C in Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Raman measurements were carried out at very low laser power to minimize possible sample deterioration or phase transition with operating time. Indeed, in previous studies [26][27][28], we clearly evidenced that phase transitions can be induced by local heating due to laser irradiation, especially with nanoscale iron oxide nanoparticles. So, in this study, we chose to work with an output laser power of 0.6 mW in order to prevent phase transformations.…”
Section: Surface Analysismentioning
confidence: 90%
“…Variations in crystallization features might support this partial decorrelation observed between the different Raman signatures of aragonite. The 100 to 1000 cm −1 fingerprint region of a Raman spectrum is extremely valuable, as the bands of this region arise from interacting vibrational modes and can thus clearly reveal modifications in local molecular environments as well as phase and crystalline structure transitions (Urmos et al 1991;Gauldie et al 1997;Beuvier et al 2012). Moreover, Morales-Nin (1987) observed that opaque and translucent zones are different in terms of width of primary increments and also in terms of thickness and size of aragonite crystals.…”
Section: Understanding the Formation Of Otolith Macrostructuresmentioning
confidence: 96%